2007
DOI: 10.1002/ab.20182
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of male and female prisoners involved in bullying behavior

Abstract: This study explores bullying behavior in a larger and more representative sample than previous prison-based research. It has two core aims, first to explore the nature of bullying in relation to indirect and direct aggression and, second, to explore the predictors of bully-category membership with particular reference to behavioral characteristics. Participants were adult men (n=728) and women (n=525) prisoners. All completed a behavioral measure of behavior indicative of bullying (Direct and Indirect Prisoner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
2
16
1
2
Order By: Relevance
“…Estimates are higher than in previous studies (e.g. Ireland, 1999;Ireland et al, 2007;Palmer and Farmer, 2002), although this is a function of the change in timeframes used, with previous research focusing on behaviour in the previous week, whereas this study focused on the previous month. Nonetheless, this study indicates evidence of high proportions and frequencies of perpetration and victimisation within prisons.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Estimates are higher than in previous studies (e.g. Ireland, 1999;Ireland et al, 2007;Palmer and Farmer, 2002), although this is a function of the change in timeframes used, with previous research focusing on behaviour in the previous week, whereas this study focused on the previous month. Nonetheless, this study indicates evidence of high proportions and frequencies of perpetration and victimisation within prisons.…”
Section: Discussioncontrasting
confidence: 81%
“…It is possible, however, that coercive aggression is actually a more accurate reflection of the consequences of aggression [Ireland et al, 2007]. Nonetheless, this study has demonstrated that it is a collection of behaviours worthy of further investigation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For the purpose of the present study, prisoners were classified according to whether they had endorsed at least one bullying item (''bully'') as victim and/or perpetrator, or had not done so. Further details of this part of the study can be found in Ireland et al [2007].…”
Section: Methodsmentioning
confidence: 99%
“…This would be consistent with considerable evidence of a sex difference in proneness to physical aggression [Archer, 2004;Eagly and Steffen, 1986;Hyde, 1986], and with other measures from the present prison sample . Whether prisoners identified as bullies would generally be more ready to respond to provocation with physical aggression irrespective of the RHP of the opponent was also assessed: this would follow if those identified as bullies are generally aggressive individuals, as identified by conventional measures of aggression [Ireland and Archer, 2004;Ireland et al, 2007]. The sample used in this study was taken from a large-scale investigation of bullying in British prisons, whose main findings concerned the incidence of bullying behavior and how this is related to a variety of other measures Ireland et al, 2007].…”
Section: Studymentioning
confidence: 99%